MEDICAL STUDENTS’ PERCEPTIONS AND TARGET NEEDS IN ENGLISH FOR SPECIFIC PURPOSES COURSES - Suci Ramadani Sikumbang; Ahmad Amin Dalimunte (Universitas Islam Sumatera Utara (UISU), 2021)
This study aims to identify the target needs of students in English for Specific Purposes (ESP) courses at a private university in North Sumatra, Indonesia. The participants in this study were 10 students majoring in medicine. This study employed a qualitative descriptive method to explain students' perspectives of the ESP courses. The research data were obtained through surveys and interviews. The findings reveal that the participants expect the ESP courses focus on the target needs of their academic and professional lives with an emphasis on drilling their skills in the four aspects of language. In addition, it also shows that students have a positive perception of the ESP courses at the university. The findings of the study also declared that the ESP program should focus on the effective use of language and improve their language skills in reading, writing, listening, and speaking.